From Self to Nonself: The Nonself Theory - Shiah, Yung-Jong (Frontiers in Psychology, 2016)
The maintenance/strength of self is a very core concept in Western psychology and is particularly relevant to egoism, a process that draws on the hedonic principle in pursuit of desires. Contrary to this and based on Buddhism, a nonself-cultivating process aims to minimize or extinguish the self and avoid desires, leading to egolessness or selflessness. The purpose of this paper is to present the Nonself Theory (NT). The universal Mandala Model of Self (MMS) was developed to describe the well-functioning self in various cultures. The end goal of the self is to attain ultimate wholeness or authentic and durable happiness. Given that the nonself is considered a well-functioning self and ultimate wholeness, the MMS is suitable for constructing the NT. The ego and nonself aspects of psychological self-functioning and their underlying processes are compared, drawing on the four concepts of the MMS: biology, ideal person, knowledge/wisdom and action. The ego engages in psychological activities to strengthen the self, applying the hedonic principle of seeking desire-driven pleasure. In contrast, a nonself approach involves execution of the self-cultivation principle, which involves three ways: giving up desires, displaying compassion, practicing meditation and seeking understanding Buddhist wisdom. These three ways have the goal of seeing through and overcoming the illusion of the self to achieve a deep transformation integrally connected to the experience of eliminating the sense of self and its psychological structures. In addition, the NT provides a comprehensive framework to account for nonself-plus-compassion-related activities or experiences such as altruism, mindfulness, mediation, mysterious/peak experiences, elimination of death anxiety and moral conduct. The NT offers possible answers that might lead to a more comprehensive understanding of human beings and the deeper meaning of life, toward the ultimate goal of ultimate wholeness. An examination of possible clinical applications and theoretical directions for future research in nonself psychology are provided.